Transparency and accountability in the justice system: Building public trust and justice: The Role of Public Trust in Fair Law Enforcement - Misnah Irvita; Asriani Asriani (Privietlab, 2025)
This study critically examines the intricate relationship between transparency, accountability, and public trust in the justice system within a changing socio-political landscape. Grounded in legal theory and employing a qualitative methodology that integrates phenomenology, ethnology, and virtual ethnography, the research explores how societal values, cultural perceptions, and institutional practices shape trust in judicial institutions. Data were collected through in-depth interviews and digital ethnographic observations involving members of the public and judicial officials. Findings reveal that transparency particularly in court decisions, budget management, judicial appointments, and public access to information significantly enhances accountability and fosters institutional legitimacy. The study also highlights how perceptions of fairness, openness, and ethical conduct of law enforcement directly impact public confidence and legal compliance. Moreover, public trust is shown to strengthen social integration and the overall effectiveness of law enforcement by encouraging community participation and reducing legal cynicism. Policy recommendations include the institutionalization of performance evaluations, transparent financial reporting, and digital platforms for public engagement. These measures are proposed as critical steps to create a responsive, equitable, and trustworthy judicial system. The study contributes to the evolving discourse on legal reform and offers actionable strategies for enhancing judicial integrity and democratic governance.